Nitrogênio mineral ou oriundo da fixação biológica em pastagem tropical: respostas na produtividade animal e emissão de metano entérico - Lima, Italo Braz Gonçalves de (2018)
In the intensification of the production systems, the input of nitrogen aims to improve the productivity and the optimization of the resources, making the system more efficient.Nitrogen (N) coming from the biological nitrogen fixation (BNF) through legumes becomes a sustainable alternative in these systems.The study aimed to evaluate the animal productivity and enteric methane emissions of Nellore heifers in pasture of Brachiaria brizantha cv. Marandu fertilized or not with nitrogen,or intercropped with Arachis pintoi cv. BRS Mandobi.An experimental trial consisting of 12 paddocks, eight paddocks consisting exclusively of Brachiaria brizantha (Hochst ex A. Rich) Stapf cv. Marandu, four of them without N input, four fertilized with 150 kg ha-1 of N and the others were intercropped with Arachis Pintoi cv. Mandobi.The experimental design was a randomized block, with three treatments and four replicates and with repeated measures over time (seasons).The measured variables were submitted to analysis of variance using PROC MIXED of SAS.The means were compared by the Student t test, at 10% probability. In autumn, forage mass, green forage mass, leaf mass, stem mass was greater in fertilized treatment compared to control and intercropped (P ≤ 0.001). The individual weight gain and gain per area in fertilized treatment was greater than control and the intercrop (P = 0.010 and P ≤ 0,001, respectively) due to the improvement in the digestibility and nutritive value of the diet.It was observed higher gain per area and stocking rate in fertilized treatment (P = 0.020 and P = 0.047, respectively), reflecting the increase of the support capacity provided by the nitrogen fertilization.In the daily and equivalent methane emissions per station there was no difference between treatments (P = 0.186 and P = 0.189, respectively).In the methane emissions by stocking was higher in the fertilized treatment compared to the control, but there was no difference of the intercropped (P = 0.001).As it was the first year of legume implantation, its contribution in the canopy was low, so the forage peanut presented improvements in the nutritive value of the diet, crude protein intake, increase in the stocking rate,but not enough to match nitrogen fertilization, being necessary new studies in canopy with more time of establishment.The use of nitrogen in pastures has a direct response in the productivity. The nitrogen input into the system allowed higher productivity per unit of area. Neither system has caused a reduction in enteric methane emissions.